EDUCATING OF COMMUNITY TO CORRDINATE INETRESTS IN SPATIAL PLANNING - Ezmale, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The main obstacles of low effectiveness of public participation in the development process of spatial planning documents in Latvia are the lack of confidence of the population in the effectiveness of public participation, the lack of adequate competence and skills of local authorities for involvement of different interest groups, insufficient understanding of society about the coordination the interests of individuals with spatial development aims in different planning levels, as well as with the aims of sustainable development of local government territory. There are a variety of informal measures and methods which the municipality can use to raise the level of public knowledge and awareness about spatial planning to achieve the best outcomes from both the public interest and sustainable development perspective. These measures help a more active involvement and effectiveness of participation of community in the spatial planning process. The purpose of the study is to describe the problems of coordination of different interests, insufficient public participation, as well as to identify the educational opportunities for the matching the different interests in spatial development planning process in Latvia. The following tasks were identified in order to achieve the objective of the study: (1) to justify the needs for the coordination of interests in the spatial planning process; (2) to identify the main problems of public involvement and educational opportunities for the coordination of the interests. Methods used - content analysis, document analysis, deductive and inductive method, comparative analysis.